THE ENGLISH TEACHERS' UNDERSTANDING OF GENRE BASED APPROACH: APPLICATION AND DIFFICULTIES IN TEACHING-LEARNING ACTIVITIES - Nurviani, Vina (2012)
This thesis reported on an investigation of English teachers' understanding of genre-based approach (see Derewianka, 1990; Gibbons, 2002, Rothery, 1988) concerning the curriculum cycle, the basic principles of genre based approach, text types, and systemic functional grammar. The study also attempted to explore the implementation of the genre-based approach in teaching-learning activities based on the English teachers' understanding and the difficulties they encountered in implementing the genre-based approach. This study employed a mix method design. All data were gained from several sources, including closed-ended and open-ended questionnaires, non-participant classroom observations conducted in eight weeks and semi structure interviews conducted immediately after the completion of all activities in the classroom observations. It was found that the English teachers' understanding of the genre-based approach still needs improvement and guidance. It can be seen from the partial implementation of the approach in teaching-learning processes. Some difficulties were also found in applying the approach related to the students' ability in comprehending and writing texts and lack of facilities. Based on the findings, it is recommended that the genre-based approach should be disseminated soon to enhance practically and conceptually the students' ability and the quality of the teaching-learning processes that are relevant to the school based curriculum. It is also recommended that further study include more participants and broaden scope.